سلطة القاضي في تعديل العقد في القانون الجزائري - سوسن خلايفية; عبير زلاقي (My University, 2023)
Abstract: The power of a judge to modify a contract is considered an exception to the general rule that governs and organizes civil contracts, which is summarized as «the law of the contracting parties», however there may be circumstances and situations, whether during the formation of the contract, such as the inclusion of vice of lesion or exploitation, or the inclusion of unfair terms that burden the consenting party, or during its execution in case of unforeseen circumstance that make the execution commitment difficult for the debtor, or in the case of a penalty clause or a judicial term. This has made the modification of the contract by the judge an inevitable necessity to restore the balance between the parties. the purpose is to mitigate the negative effects resulting from the will of the parties on one hand, and to achieve contractual balance and contractual justice on the other hand. .................................................................. الملخــص: سلطة القاضي في تعديل العقد يعتبر خروجا عن القاعدة العامة التي تحكم و تنظم العقود المدنية، و المتمثلة في "العقد شريعة المتعاقدين"، فإذا كانت إرادة الأطراف هي الأساس في إبرام العقود و إعطائها الوصف القانوني المنشود، فإنه قد تطرأ ظروف و أحوال سواء في مرحلة تكوين العقد كأن يتضمن العقد عيبا الغبن أو الإستغلال، أو أن يتضمن شروطا تعسفية ترهق الطرف المذعن، أو مرحلة تنفيذه و ذلك في حال حدوث ظرف طارئ يجعل تنفيذ الإلتزام مرهقا للمدين، أو في حال الشرط الجزائي و كذا الأجل القضائي، و هذا ما جعل تعديل القاضي للعقد ضرورة حتمية لإعادة التوازن بين أطرافه، فيتدخل قصد التخفيف من الآثار السلبية الناتجة عن إرادة الأطراف من ناحية و بهدف تحقيق التوازن العقدي و تحقيق العدالة العقدية من ناحية أخرى ترجة باللغة الانجليزية ........................................................................ Résumé: Le pouvoir du juge de modifier un contrat est considéré comme une exception à la règle générale qui régit et organise les contrats civils, qui se résume à ce que « le contrat est la loi des contractants », cependant, il peut y avoir des circonstances et des situation que ce soit lors de la formation du contrats, telles que l’inclusion d’un vice de lésion ou d’exploitation, ou l’inclusion des clauses abusives qui pèsent sur la partie consentante, ou lors de son exécution, en cas de circonstance imprévues qui rendent l’exécution de l’engagement difficile pour le débiteur, ou en cas de clause pénale et de terme juridique, cela a rendu la modification du contrat par le juge une nécessité inévitable pour rétablir l’équilibre entre les parties, le but est d’atténuer les effets négatifs de la volonté des parties d’une part, et d’atteindre l’équilibre contractuel et la justice contractuelle d’autre part.